Associations of unprocessed and processed meat intake with mortality and cardiovascular disease in 21 countries [Prospective Urban Rural Epidemiology (PURE) Study]: a prospective cohort study - (:unkn) unknown (OXFORD UNIV PRESS, 2021)
Background: Dietary guidelines recommend limiting red meat intake because it is a major source of medium- and long-chain SFAs and is presumed to increase the risk of cardiovascular disease (CVD). Evidence of an association between unprocessed red meat intake and CVD is inconsistent. Objective: The study aimed to assess the association of unprocessed red meat, poultry, and processed meat intake with mortality and major CVD. Methods: The Prospective Urban Rural Epidemiology (PURE) Study is a cohort of 134,297 individuals enrolled from 21 low-, middle-, and high-income countries. Food intake was recorded using country-specific validated FFQs. The primary outcomes were total mortality and major CVD. HRs were estimated using multivariable Cox frailty models with random intercepts. Results: In the PURE study, during 9.5 y of follow-up, we recorded 7789 deaths and 6976 CVD events. Higher unprocessed red meat intake (>= 250 g/wk vs. <50 g/wk) was not significantly associated with total mortality (HR: 0.93; 95% CI: 0.85, 1.02; P-trend = 0.14) or major CVD (HR: 1.01; 95% CI: 0.92, 1.11; P-trend = 0.72). Similarly, no association was observed between poultry intake and health outcomes. Higher intake of processed meat (>= 150 g/wk vs. 0 g/wk) was associated with higher risk of total mortality (HR: 1.51; 95% CI: 1.08, 2.10; P-trend = 0.009) and major CVD (HR: 1.46; 95% CI: 1.08, 1.98; P-trend = 0.004). Conclusions: In a large multinational prospective study, we did not find significant associations between unprocessed red meat and poultry intake and mortality or major CVD. Conversely, a higher intake of processed meat was associated with a higher risk of mortality and major CVD.
Keywords: unprocessed red meat; poultry; processed meat intake; mortality; cardiovascular disease; cohort study; CORONARY-HEART-DISEASE; RISK-FACTORS; ALL-CAUSE; RED MEAT; CONSUMPTION; METAANALYSIS; STROKE